Family Chodecki and the Moldavian expedition from 1509 - Niemczyk, Katarzyna (Balcanica Posnaniensia. Acta et studia, 2018)
This article refers to the problem of the relations between Kingdom of Poland and Moldova, especially to the 1509-year conflict and the role the Chodecki’s family played in it. Bogdan III – hospodar of Moldova who was desperately trying to find an ally, was able to give Pokuttya back to Poland in exchange for Polish agreement for his marriage with king’s sister Elisabeth. The mother and namesake of the latter - Elisabeth Habsburg didn’t accept this proposal. Bogdan however counted on support from Stefan of Chodcza. As a result of conducted negotiations the former got Pokuttya back to Poland. However, he didn’t receive Elisabeth’s hand. Bogdan blamed Stanislaw of Chodcza for this failure. The 1509 expedition was meant as revenge not only on Poland but also on Chodecki’s family.